KERAGAMAN JENIS SERANGGA PADA PERTANAMAN STROBERI DI DESA RURUKAN KOTA TOMOHON - Estu N. Soeratman; Noni N. Wanta; Emmy Senewe; Robert W. Tairas (COCOS, 2015)
ABSTRACT This study aims to determine the diversity of insects associated to the cultivation of strawberries in Rurukan village of Tomohon. The sampling method used in this study is a relative method. Insect samples obtained from the arrest through some of pit fall traps and yellow sticky traps, were collected, counted and categorized to be identified. The diversity values calculated using the Shannon-Wiener diversity index (H) and Pielou evenness index (E). The results showed that insects caught in pit fall traps there are four of the Order is the order Hymenoptera, Coleoptera, Diptera and Orthoptera while insects found in yellow sticky traps consists of seven orders of 26 families and 27 species of insects. The seventh order of insects found are of the order Thysanoptera, Diptera, Hymenoptera, Coleoptera, Homoptera. Hemiptera, and Lepidoptera. Insects dominated by the order Diptera comprising 11 species (41%), Hymenoptera 10 species (37%), Hemiptera 2 types (7%) and the order Homoptera, Thysanoptera and Lepidoptera each 1 species (4%). The diversity index value of insects in the first and second observation is H '= 2.46 and H' = 2,45, or in other words that environmental conditions on strawberry plants in the village Rurukan in a state of being. While the value of the Evenness index (E ') to the first observation is E' = 0.79 and the second E '= 0.75. The results showed that the community of insects found on strawberry plants in rural areas Rurukan in stable condition with insects uniform